2009
DOI: 10.1007/s12598-009-0120-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical hydrogen storage performance of AB5-CoB composites synthesized by a simple mixing method

Abstract: AB 5 (MlNi 4.0 Al 0.3 Cu 0.5 Zn 0.2 ) alloy and CoB alloy were prepared by arc melting. AB 5 -CoB composites were synthesized by simple mixing of AB 5 alloy powders and CoB alloy powders, and their electrochemical hydrogen storage properties were studied as negative electrodes in KOH aqueous solution. The maximum discharge capacity of the AB 5 -CoB(50%) composite (the content of CoB in the composite is 50 wt.%) reached 365.3 mAh⋅g −1 . After 100 charge-discharge cycles, the discharge capacity of the AB 5 -CoB(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…80 However, no synergistic effects were reported, although they found that the composite of Co-Si 3 N 4 as an additive in an electrode containing a PrMg 12 hydrogen storage alloy presented good catalytic ability and thus a significant increase in discharge capacity. Similar reports have been made for composites of La 2 Mg 17 alloy and Co, 81 La-Mg-Ni-based and Co-C alloys, 82 LaNi 5 -based and CoB alloys, 83 and LaNi 5 -based alloy and Co. 84 Two discharge plateaus occur for these composites. The first plateau is caused by hydrogen desorption from the hydrogen storage alloy and the second plateau is due to the oxidation of Co or Co-based alloys.…”
Section: Composite Materialssupporting
confidence: 83%
“…80 However, no synergistic effects were reported, although they found that the composite of Co-Si 3 N 4 as an additive in an electrode containing a PrMg 12 hydrogen storage alloy presented good catalytic ability and thus a significant increase in discharge capacity. Similar reports have been made for composites of La 2 Mg 17 alloy and Co, 81 La-Mg-Ni-based and Co-C alloys, 82 LaNi 5 -based and CoB alloys, 83 and LaNi 5 -based alloy and Co. 84 Two discharge plateaus occur for these composites. The first plateau is caused by hydrogen desorption from the hydrogen storage alloy and the second plateau is due to the oxidation of Co or Co-based alloys.…”
Section: Composite Materialssupporting
confidence: 83%
“…Critical applications of Co 2 B in a variety of reactions resulting from its functional properties gained significant attention [ 11 ]. The antioxidant effect of boron and the high electrochemical properties of cobalt makes Co 2 B a candidate catalyst for fuel cell and hydrogen storage applications [ 12 , 13 ]. The oxidation resistance properties of Co 2 B also make the compound a good option for surface coating applications [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In numerous cobalt-based alloys, Co-B alloys have attracted extensive attention because of their excellent electrochemical performance. The researchers have been trying to find Co-B alloys with better cycle stability, higher electrochemical capacity, and higher rate discharge-ability used as negative electrode materials for alkaline secondary batteries based on the optimization of preparation methods [11,12], the select of raw materials [3], the control of the synthesizing conditions [13] and multi-component alloying [8,14,15,16].…”
Section: Introductionmentioning
confidence: 99%